Understanding the Information Requirements of Arts and Humanities Scholarship - Agiatis Benardou; Panos Constantopoulos; Costis Dallas; Dimitris Gavrilis (International Journal of Digital Curation, 2010)
This paper reports on research of scholarly research practices and requirements conducted in the context of the Preparing DARIAH European e-Infrastructures project, with a view to ensuring current and future fitness for purpose of the planned digital infrastructure, services and tools. It summarises the findings of earlier research, primarily from the field of human information behaviour as applied in scholarly work, it presents a conceptual perspective informed by cultural-historical activity theory, it introduces briefly a formal conceptual model for scholarly research activity compliant with CIDOC CRM, it describes the plan of work and methodology of an empirical research project based on open-questionnaire interviews with arts and humanities researchers, and presents illustrative examples of segmentation, tagging and initial conceptual analysis of the empirical evidence. Finally, it presents plans for future work, consisting, firstly, of a comprehensive re-analysis of interview segments within the framework of the scholarly research activity model, and, secondly, of the integration of this analysis with the extended digital curation process model we presented in earlier work.